The Influence of State Capital Participation, Company Size, Environmental Costs, and Company Ownership Structure on The Financial Performance of BUMN in 2019-2023 - Pyara Tri Amanda; Saring Suhendro (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to provide empirical evidence of the influence of state capital participation, company size, environmental costs, and company ownership structure on the financial performance of state-owned enterprises. This test uses a statistical tool, namely IBM SPSS version 25. The population in this study were all state-owned companies or BUMN, namely 113 companies and the sample selection used the purposive sampling method so that 31 companies were selected. The analysis methods used were descriptive statistical analysis, classical assumption test, multiple linear regression analysis, coefficient of determination, F test, and t test. The coefficient of determination of 0.58 indicates the ability of the independent variable to explain the dependent variable by 58%.